Structure, thermal and mechanical properties of poly (ε-caprolactone)/organomodified clay bionanocomposites prepared in open air by in situ polymerization. Issue 12 (1st December 2020) - Elghaoui, H.; Hrichi, S.; Raihane, M.; Arous, M.; Bouharras, F. Z.; Verdejo, R.; Beniazza, R.; Ilsouk, M.; Lopez-Manchado, M. A.; Lahcini, M.
Abstract: The first example of the usefulness of titanium (IV) butoxide, as initiators for open air in-situ intercalative polymerization of ε-caprolactone (ε-CL) in the presence of organoclay is herein reported. The bionanocomposites based on poly(ε-caprolactone) (PCL) were prepared by in-situ Ring Opening Polymerization (ROP) of ε-caprolactone in the presence of different organomodified montmorillonite clay (ODA-MMT) loading (1, 3 and wt%). Structural, thermal and mechanical characterizations of the resulting bionanocomposites were investigated. The presence of the nanoclay increased PCL crystallinity, melting temperature and thermal stability, whereas some decrease in Tg was observed. TEM analyses confirmed the good dispersion of ODA-MMT with 1 and 3 wt% content into the PCL polymer as already asserted by XRD diffraction. Finally, the Young's modulus of the PCL nanocomposites was higher compared to the neat PCL, while a decrease of stress and strain at break for materials with different filler content was observed. Graphical Abstract: